Detection of violent activity in surveillance system using different deep learning techniques - Chakravorty, Tirthendu Prosad; Abeer, Mobashra; Baroi, Shaiane Prema; Roy, Sristy (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.